2008
DOI: 10.1186/1471-2148-8-58
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic position of the langur genera Semnopithecus and Trachypithecus among Asian colobines, and genus affiliations of their species groups

Abstract: BackgroundThe evolutionary history of the Asian colobines is less understood. Although monophyly of the odd-nosed monkeys was recently confirmed, the relationships among the langur genera Presbytis, Semnopithecus and Trachypithecus and their position among Asian colobines remained unclear. Moreover, in Trachypithecus various species groups are recognized, but their affiliations are still disputed. To address these issues, mitochondrial and Y chromosomal sequence data were phylogenetically related and combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
123
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 36 publications
(38 reference statements)
8
123
1
4
Order By: Relevance
“…Additionally, the kipunji cranium offers no evidence of hybrid ancestry. But there is no reason to expect classic hybrid traits (e.g., supernumerary teeth; Ackermann et al, 2006) in a lineage that has had thousands of generations to weed out conflicts between its parental genomes, as witnessed by the fact that the kipunji and other such suspected hybrid taxa have been identified solely on the basis of their DNA (Tosi et al, 2000;Sinha et al, 2005;Chakraborty et al, 2007;Karanth, 2008;Karanth et al, 2008;Osterholz et al, 2008;Burrell et al, 2009;Zinner et al, 2009). …”
Section: Kipunji Evolutionary Relationships and Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the kipunji cranium offers no evidence of hybrid ancestry. But there is no reason to expect classic hybrid traits (e.g., supernumerary teeth; Ackermann et al, 2006) in a lineage that has had thousands of generations to weed out conflicts between its parental genomes, as witnessed by the fact that the kipunji and other such suspected hybrid taxa have been identified solely on the basis of their DNA (Tosi et al, 2000;Sinha et al, 2005;Chakraborty et al, 2007;Karanth, 2008;Karanth et al, 2008;Osterholz et al, 2008;Burrell et al, 2009;Zinner et al, 2009). …”
Section: Kipunji Evolutionary Relationships and Systematicsmentioning
confidence: 99%
“…Several cercopithecid species are thought to have arisen through intrageneric introgression (Tosi et al, 2000;Chakraborty et al, 2007;Osterholz et al, 2008), and intergeneric hybridization has been reported in both captivity and (less frequently) the wild (Markarian et al, 1972;Chiarelli, 1973;Dunbar and Dunbar, 1974;Jolly et al, 1997). Like the kipunji, the golden and capped leaf monkeys (Trachypithecus geei and T. pileatus) of South Asia are proposed to have arisen through intergeneric hybridization between Semnopithecus and Trachypithecus (Karanth, 2008;Karanth et al, 2008;Osterholz et al, 2008). These cases suggest that natural hybridization has been more important in Old World monkey evolution than previously thought (Arnold and Meyer, 2006) and also raise interesting questions for taxonomists.…”
Section: Kipunji Evolutionary Relationships and Systematicsmentioning
confidence: 99%
“…Though the monophyly of the odd-nosed monkey group has been unambiguously established from previous studies of both morphology and geographical distribution [1,11,12,14,60] and confirmed by genetic data [17][18][19]26,30,31,52], there had long been controversy over the relationships among the genera within this group. It was especially the case that among Pygathrix, Rhinopithecus and Nasalis (Figure 3) [17][18][19]26,30,31,48].…”
Section: Intergeneric Relationships Within Asian Presbytinamentioning
confidence: 99%
“…Trachypithecus is the largest and most diverse genus of Asian Presbytina with a widest distribution, ranging from South India and Sri Lanka through mainland Southeast Asia to the Sundaland [52]. Within genus Trachypithecus, one species that had long been considered hard to determine phylogenetically is T. pileatus (the capped langur).…”
Section: Interspecies Relationships Within Asian Presbytinamentioning
confidence: 99%
See 1 more Smart Citation